Exploration of in vitro thrombolytic, anthelminthic, cytotoxic and in vivo anxiolytic potentials with phytochemical screening of flowers of Brassica nigra - Mohammad Sarowar Uddin; Md. Shalahuddin Millat; Mohammad Safiqul Islam; Md. Saddam Hussain; Md. Giash Uddin; Shafayet Ahmed Siddiqui; Mahmuda Ferdous (SpringerOpen, 2020)
Abstract Background Brassica nigra is a plant of Brassicaceae family, which possesses numerous medicinal values. Our present study is intended to assess the potential in vitro thrombolytic, anthelminthic, cytotoxic and in vivo anxiolytic properties of MCE of B. nigra flowers. MCE was fractioned for separating the compound on the basis of polarity by using chloroform, n-hexane and ethyl acetate solvent. Thrombolytic and anthelminthic activities were explained by collecting human erythrocytes and earthworms as test models, respectively. Anxiolytic activity was evaluated by elevated plus maze and hole board models while cytotoxic test was conducted through brine shrimp lethality bioassay. Results MCE revealed the presence of alkaloids, flavonoids, tannin, diterpenes, glycosides, carbohydrates, phenols, fixed oils and fat. In case of thrombolytic test, the MCE, CSF, ASF and n-HSF had produced maximum clot lysis activity at 5 and 10 mg/ml dose conditions. Two different concentrations (10 and 20 mg/ml) of MCE and its fractions showed significant (p < 0.05) anthelminthic activities in a dose-dependent manner. Significant anxiolytic activity was observed for all fractions which was comparable to the standard drug diazepam (p < 0.05). Again, the cytotoxic screening also presented good potentials for all fractions. Conclusion From the findings of present study, we can conclude that MCE of B. nigra flowers and its fraction possess significant anxiolytic, anthelmintic, anticancer and thrombolytic properties which may be a good candidate for treating these diseases through the determination of bio-active lead compounds.